The performance of concrete using fly ash and bottom ash as partially replacement of cement and fine aggregate - Wayrah, Mohamed Yusuf (2019)
Concrete is one of the oldest manufactured construction material used in construction of various structures around the world. Due to its high demand, the material used for concrete production depleting every year. Nowadays, demand for cement sand and gravel continues to increase in concrete production. Excessive sand mining will lead to the degradation of riverine environment. An indiscriminate and illegal sand mining has created many problems in the environmental setting and water quality of the river basin. In this study, local power plant waste was used as replacement of cement and fine aggregate. This investigation is carried out to investigate the performance of concrete using fly ash and bottom. There are 3 types of mix Used in this study and the percentage of fly ash is fixed on 25% and while the bottom ash ranges between 0%, 5%, and 10%.The cement and fine aggregate replacement level were cast before subjected to water curing for 7, and 28 days. Slump test, compressive strength test, and flexural strength were conducted in accordance to the existing standard. The slump value decreased with increase in the replacement level of sand by bottom ash. The percentage of water absorption of the concrete increased with increase in the replacement level of sand by bottom ash. Respectively. Besides that, concrete with 10% coarse aggregate replacement achieved a high compressive strength which is 34.436 N/mm2. In flexural strength test, the concrete beam with 0% replacement also achieved the highest flexural strength with 3.5.648 N/mm2. The optimum fine aggregate replacement in this research is 10% replacement as it still achieved the maximum requirement strength of concrete and is suitable in typical reinforced concrete application in building which intended working life is at least 50 years.